ANALYSIS OF WOMEN’S PARTICIPATION IN RAINFED RICE AGRICULTURAL SYSTEMS IN GEBANGANGKRIK VILLAGE OF NGIMBANG LAMONGAN, EAST JAVA - Sutrisno, Eko; Sari, Poppy Diana (MUWAZAH, 2016)
The aim of this study was to obtain in-depth information about the participation of women farmers in agricultural production in the village of Gebangangkrik. Women in the village of Gebangangkrik go to work in the fields to help their husbands, from land preparation to post harvest process. Fees earned by women is lower than for men. They work with a rotation system or alternately between families or between neighbors that do not receive fees or spend big except for breakfast. There are many women farmers who worked to pay the debt, because when the bad season come, they had to borrow rice to other people who had more extensive rice fields with the assurance will voluntarily to help work in the fields when the next planting season. However, women farmers access to information in the field of agriculture is still very limited, so it seems that the girls were just as workers.Penelitian ini bertujuan untuk mendapatkan informasi yang mendalam tentang partisipasi perempuan petani dalam produksi pertanian di Desa Gebangangkrik. Perempuan di Desa Gebangangkrik ikut bekerja di sawah membantu suami, dari proses penyiapan lahan hingga pascapanen. Upah yang diterima oleh para perempuan lebih rendah daripada laki-laki. Mereka bekerja dengan sistem giliran atau bergantian antar keluarga atau antar tetangga sehingga tidak menerima upah atau mengeluarkan biaya besar kecuali untuk sarapan. Terdapat banyak perempuan petani yang bekerja karena untuk membayar utang, sebab saat musim paceklik sudah pinjam beras kepada orang yang memiliki sawah lebih luas dengan jaminan mau disuruh membantu bekerja di sawah saat musim tanam selanjutnya. Namun begitu, akses para perempuan petani untuk mendapatkan informasi di bidang pertanian masih sangat sedikit, sehingga terkesan bahwa para perempuan tersebut hanya sebagai pekerja.